Microbiological evaluation of antibacterial potentiality of some edible plant extracts against multidrug resistant (MDR) human pathogens (International Current Pharmaceutical Journal, 2014)
Antimicrobial resistance is a subject of great concern in public health and also in the designing of strategies for current therapeutic protocols all over the world. Plants used for traditional medicine contain a wide range of substances which can be used to treat various infectious diseases. Hence, antibacterial activities of aqueous extracts of 10 plant species were studied against 25 multidrug resistant (MDR) clinical isolates using the agar well diffusion method. The most resistant organisms were Acinetobacter baumanii (A. baumanii) (resistant to 16 different antibiotics), Enterococcus faecium (E. faecium) (resistant to 15 different antibiotics), Pseudomonas aeruginosa (P. aeruginosa) (resistant to 15 antibiotics), Gemella morbillorum (G. morbillorum) (resistant to 14 different antibiotics), Enterobacter cloacae (E. cloacae) (resistant to 13 different antibiotics) respectively. Among the tested plant extracts, only extracts of Allium cepa, Allium sativum, Foeniculum vulgare, Matricaria chmomilla, Salvia offcinalis and Thymus Vulgaris showed strong antibacterial activity against MDR isolates with inhibition zones ranging from 8.33 to 26 mm. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the most active plant extracts; Allium cepa and Foeniculum vulgare were ranged from 0.062 to 0.25 mg/ml and 0.031 to 0.125 mg/ml, respectively. Foeniculum vulgare extract was bactericidal for all bacteria while Allium cepa extract was bacteriostatic. Hence, the discovered compounds from these plants can use as templates for the development of new antibacterial agents.DOI: http://dx.doi.org/10.3329/icpj.v4i1.21162 International Current Pharmaceutical Journal, December 2014, 4(1): 336-339